2022
DOI: 10.3390/cells11172743
|View full text |Cite
|
Sign up to set email alerts
|

Immune Determinants of Viral Clearance in Hospitalised COVID-19 Patients: Reduced Circulating Naïve CD4+ T Cell Counts Correspond with Delayed Viral Clearance

Abstract: Virus-specific cellular and humoral responses are major determinants for protection from critical illness after SARS-CoV-2 infection. However, the magnitude of the contribution of each of the components to viral clearance remains unclear. Here, we studied the timing of viral clearance in relation to 122 immune parameters in 102 hospitalised patients with moderate and severe COVID-19 in a longitudinal design. Delayed viral clearance was associated with more severe disease and was associated with higher levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…SARS-CoV-2-specific CD4 + T cells were associated with ameliorated COVID-19 disease severity, and the induction of SARS-CoV-2-specific CD4 + T cells was correlated with rapid decrease of viral load ( 62 , 63 ). Another study also confirmed that early viral clearance and less critical illness were correlated with the higher counts of CD4 + T cells, particularly naïve CD4 + T cells ( 64 ).…”
Section: Immune Responses In Covid-19mentioning
confidence: 72%
“…SARS-CoV-2-specific CD4 + T cells were associated with ameliorated COVID-19 disease severity, and the induction of SARS-CoV-2-specific CD4 + T cells was correlated with rapid decrease of viral load ( 62 , 63 ). Another study also confirmed that early viral clearance and less critical illness were correlated with the higher counts of CD4 + T cells, particularly naïve CD4 + T cells ( 64 ).…”
Section: Immune Responses In Covid-19mentioning
confidence: 72%
“…Samples were retrospectively included to be tested with five WGS protocols. Samples were previously sent to the Clinical Microbiological Laboratory of the Leiden University Medical Center (LUMC, The Netherlands) for nucleotide extraction and SARS-CoV-2 E-gene PCR testing [ 23 ] in the period March–October 2020 (Wuhan-like viruses circulating). After nucleotide extraction and PCR, samples were stored at ° C until further distribution between different centers for WGS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Early SARS‐CoV‐2‐specific CD4+ T cells in the blood were associated with relatively milder disease 37 . Additionally, higher levels of CD4 T cells were associated with early viral clearance and milder COVID‐19 symptoms 38 . We presumed that increased CSF volume was positively correlated with the number of immune cells, which prevents the occurrence of more severe respiratory symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…37 Additionally, higher levels of CD4 T cells were associated with early viral clearance and milder COVID-19 symptoms. 38 We presumed that increased CSF volume was positively correlated with the number of immune cells, which prevents the occurrence of more severe respiratory symptoms. Several retrospective studies have also found an association between the inferior temporal area and COVID-19.…”
Section: Discussionmentioning
confidence: 99%